Relatório do estágio curricular supervisionado em medicina veterinária – área de clínica cirúrgica de pequenos animais - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This report describes the activities monitored / developed by the academic Bruna Gonzalez dos Santos, with Prof. Dra. Maria Ligia de Arruda Mistieri. The chosen practice area was the small animal surgical clinic, in which follow-up of the clinical care routine focused on surgical cases and surgical procedures themselves. The same was done in two locations interest. The first location was the Dr. Guilherme Savassi Surgical Dog and Cat Clinic, located in Belo Horizonte / MG - Brazil, under the supervision of Dr. Guilherme Savassi. In this location, the internship period was from August 6, 2018 to September 2018, totaling 272 practical hours. The second place of choice was the Hospital Veterinary Clinics of the Federal University of Rio Grande do Sul (HCV / UFRGS), located in Porto Alegre / RS - Brazil, under the supervision of Prof. Dr. Cristiano Gomes. In this location, the internship period was from October 1, 2018 to January 1 November 2018, totaling 184 practical hours. Thus, the total internship period was from August 6, 2018 to November 1, 2018, with a daily workload of 8 hours, making a total of 456 practical hours.
Report of supervised curricular internship in veterinary medicine - small animal surgical clinic area
Keywords: Veterinary medicine; Cirurgia veterinária; Pequenos animais; Procedimento cirúrgico; Medicina Veterinária; Veterinary surgery; Small animals; Surgical procedure; CNPQ::CIENCIAS AGRARIAS